Post-Stroke Thalamic Syndrome (Review) - S. A. Perepelitsa; T. A. Tumilovich; A. A. Shcherbakova (Общая реаниматология)
Pain management is a foreground task of physicians specializing in various disciplines. Special attention is paid to the issues of early comprehensive rehabilitation of post-stroke patients and prophylaxis of probable long-term complications related to injuries of different brain structures.Post-stroke thalamic syndrome is the most frequent multiform complication that requires multidisciplinary efforts. Understanding of the morbid physiology of pain thalamic syndrome is the cornerstone of successful management providing higher quality of patients’ life. Currently, profound changes have taken place in the prophylaxis, diagnosis, and management of post-stroke thalamic syndrome. This review highlights the most common types of pain experienced by patients after thalamic stroke, presents morbid physiological mechanisms of pain development depending on the location of ischemic brain injury, and discusses the issues of up-to-date management and rehabilitation of post-stroke thalamic syndrome patients.